A novel design of an automation system for an energy-efficient polygeneration plant - Carandang, Vince William P. (Animo Repository, 2019)
Polygeneration plants are a leading means of increasing the efficiency and reducing the environmental impact of energy conversion. This study addresses the lack of studies on automation and control of systems that produce electricity, heating, cooling, and potable water. Mixed integer linear programming (MILP) optimization of the annualized total cost is used to select and size the plant components. The final layout consists of solar photovoltaic (PV) and thermal, an absorption chiller and a multi-effect desalination for electricity, heating, cooling and water, respectively. As auxiliary sources, boiler, gas turbine and grid connection are present. Storage units for electricity, heating, and water are also included in the proposed layout. The control and automation system are implemented using ladder logic. Sufficient supply, efficient resource use, financial gain, and real-world factors such as equipment degradation and response delay are considered in the control scheme design. Applying the methodology to a mixed industrial, commercial and residential zone in Southern Luzon, Philippines, the simulation results show successful implementation of all control scenarios. Economic analysis on the hourly cash flows of the system on a typical day show significant daily savings that outweigh the investment cost of the proposed control and automation system with monthly savings of P25,112.40 and payback period of 0.4 years. © 2019, The Authors.